A Framework for Assessing the Effectiveness of Carbon Storage Change During the Process of Land Consolidation - Changdong Ye; Pingping Deng; Chunpeng Ke; Xiaoping Fu; Jiyang Mi; Long Zhou (Land)
Land consolidation (LC) plays an important role in disturbing carbon storage (CS) change. Evaluating how LC affects CS is crucial for mitigating global climate change. However, existing research often overlooks differences in various aspects of land remediation, making it challenging to propose targeted policy adjustments to enhance CS effectiveness. This study presents a framework to assess the effectiveness of CS changes throughout the LC process, encompassing policy formulation stages (PF), construction stages (CO), and post-management stages (PM). Carbon density, a key factor in measuring CS changes, is adjusted using biomass model-integrated empirical measurements with dynamic growth coefficients calibrated through phenological monitoring. The Guangdong Demolition and Reclamation (D&R) project, a specific type of LC, serves as a case study. The findings are as follows: (1) D&R increased forest and garden land by 1420 hm2 and 1674 hm2, respectively, leading to a regional CS increase of 359,000 t, a five-fold rise per hectare. (2) The effectiveness of PF is 5.81%, with a discrepancy of over 36 million tons. The policy content’s adaptability is low, indicating significant room for improvement in CS outcomes at this stage. (3) The effectiveness of CO is 24.71%, with considerable variation between counties, ranging from 1.26% to 97.55%, due to the varying capabilities of executors and the diverse regional topographical features. Refining implementation content and encouraging collaborative efforts are effective strategies to enhance CS. (4) The effectiveness of PM is 65.03%, and the counties in the east are lower than the west. Scientific post-care is essential for improving CS. This framework provides theoretical support for optimizing LC to enhance regional CS and lays the groundwork for future investigations into the long-term impacts of LC on CS, as well as the potential for applying the methods used in this study to other regions and types of land consolidation projects.